Efficacy of Danazol Versus Panadol In Management Of Resistant Mastalgia - Maila Aslam, Farid Ullah Khan, Tahir Mirza, Ghazala Huma, Ansar Latif (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the effectiveness of Danazol versus Panadol in the treatment of mastalgia. Study Design: Prospective Study. Place and Duration: Combined Military Hospital, Peshawar; from February 2022 to March 2023 Methods: Total 54 women with range age 18-42 years presented in this study. Female patients of reproductive age group with moderate to severe breast pain and resistant cases (taken analgesia for 3 months) were included. Age, body mass index, place of residence, level of education and marital status were among the many comprehensive demographics obtained after receiving informed written consent from enrolled patients. Women were equally divided in two groups I received Danazol 100mg oral twice a day and group II received Panadol oral in 27 patients for 3-months. Post-treatment effectiveness among both groups was compared. SPSS 20.0 was used to analyze all data. Results: In all 54 females, 22 (40.7%) had age 28-30 years, 18 (33.3%)cases had age 31-40 years and 14 (25.9%) cases had age 41-42 years. In group I mean BVMI was 22. 11±4.28 kg/m2and in group II mean BMI was 21.7±6.30 kg/m2. We found a significantly excellent results in group I among 21 (77.8%) cases in terms of reduction in breast pain, as compared to group II in 15 (55.6%) cases with P value <0.004. Frequency of menstrual problem, weight gain and hirsutism was higher 11 (40.7%) as compared to Danazol group in 9 (33.3%) cases but did not found any significant difference. Practical implication: Effective use of Danazol reduces the need for Panadol. Therefore, there will be a decrease in Panadol Overuse. Conclusion: We concluded in this study that use of Danazol in the treatment of resistant mastalgia was effective and useful as compared to Panadol in terms of pain retrieve and less recurrence rate. Keyword: Mastalgia, Danazol, Panadol, Side Effects, Recurrence, Resistance